Amphiphilic Cationic Phthalocyanines for Photodynamic Therapy of Cancer. Issue 9 (26th July 2022) - Halaskova, Marie; Kostelansky, Filip; Demuth, Jiri; Hlbocanova, Ingrid; Miletin, Miroslav; Zimcik, Petr; Machacek, Miloslav; Novakova, Veronika
Abstract: Effective interaction with biomembranes is essential for activity of photosensitizers; however, majority of them are highly charged symmetrical species. Amphiphilic cationic phthalocyanines differing in bulkiness of substitution on lipophilic part (‐H, ‐SMe, ‐S t Bu) were therefore prepared. Compounds had high singlet oxygen production ( Φ Δ =0.38–0.46, DMSO), good fluorescence emission ( Φ F =0.21–0.26, DMSO), and log P values ranging −0.07–1.1 (1‐octanol/PBS). Study of interaction with liposomes revealed that also bulky ‐S t Bu derivatives are able to enter biomembranes. Detail in vitro studies (toxicity, subcellular localization, type of cell death, and morphology) were performed. Compounds were characterized by excellent EC50 values in range of dozens of nM (HeLa, EA.hy926, MCF‐7, HCT116), which were dependent on drug‐light interval and reached plateau after 4 h on HeLa cells. Well‐balanced lipophilicity with ability to interact with biomembranes rank these derivatives among perspective photosensitizers, even for vascular‐targeted PDT (VTP) since they kill EA.hy926 without any preincubation time. Abstract : Prepared amphiphilic phthalocyanines with alkylsulfanyl groups at their lipophilic part provided efficient photosensitizers with good spectral and photophysical parameters, well‐balanced lipophilicity, and ability to enter lipid bilayers. In vitro experiments on EA.hy926 cells using different drug‐light intervals (0–12 h) provided preview to their potential to be used in vascular‐targeted photodynamic therapy (VTP).